Weather-resistant ABS alloy and preparation method thereof
By adding modified polycarbonate and modified carbon nanotubes to ABS materials, and using specific preparation methods, the problem of poor weather resistance of traditional ABS materials has significantly improved the strength, toughness and flame retardant performance of the material. Application of harsh environment.
Patent Information
- Application Number
- CN202411661066.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-20
AI Technical Summary
Traditional ABS materials have poor weather resistance under long-term exposure to ultraviolet rays, humid and heat environments or chemicals, resulting in aging, discoloration and even brittle cracking, limiting their application in outdoor and harsh environments.
A weather -resistant ABS alloys include 20-22 quality portion ABS, 60-66 quality modified polycarbonate, 4 to 6 quality modified carbon nanotubes, 0.2 ~ 0.4 quality antioxidants, 0.5 0.5 ~ 1.5 Quality acid lubricants, and through specific preparation methods, including high -speed stirring, decompression distillation, and extruded granules to ensure the uniformity and performance optimization of the material.
It has significantly improved the strength, toughness and flame retardant performance of ABS alloy, enhanced its impact resistance at low temperature conditions, and improved the overall weather resistance and application range of the material.
Smart Images

Figure BDA0005143361540000121 
Figure BDA0005143361540000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ABS materials, and in particular to a weather-resistant ABS alloy and a preparation method thereof. Background Art
[0002] Acrylonitrile-butadiene-styrene copolymer (ABS) is widely used in the fields of automobiles, home appliances, electronic products, etc. due to its excellent mechanical properties, easy processing and good surface gloss. However, traditional ABS materials have the problem of poor weather resistance. When exposed to ultraviolet rays, hot and humid environments or chemicals for a long time, they will age, discolor or even crack, which seriously limits their application in outdoor and harsh environments.
[0003] In order to overcome the above defects, researchers have tried to improve the weather resistance of ABS by adding other polymers. Among them, polycarbonate (PC), as an engineering plastic with excellent transparency, heat resistance and impact strength, has become one of the ideal choices for enhancing the weather resistance of ABS. Polycarbonate (PC for short) is a high molecular polymer containing carbonate groups in the molecular chain. According to the structure of the ester group, it can be divided into aliphatic, aromatic, aliphatic-aromatic and other types. Among them, due to the low mechanical properties of aliphatic and aliphatic-aromatic polycarbonates, their application in engineering plastics is limited. At present, only aromatic polycarbonate has been industrialized. However, the rigid benzene ring structure of aromatic polycarbonate limits the orientation of PC molecular chains. After being acted upon by external forces, the orientation is not easy to relax, the residual internal stress of the molecular chain is difficult to eliminate, and the internal stress is frozen, which makes PC products prone to stress cracking. The impact performance of PC below 0°C is poor, and the impact strength at low temperature is much lower than that at room temperature. Therefore, it is necessary to improve the low-temperature toughness of PC. In order to make the modified ABS material suitable for application scenarios with strict fire protection requirements, such as internal components of public transportation vehicles, the flame retardancy problem of ABS alloy also needs to be solved.
[0004] In recent years, carbon nanotubes (CNTs) have also received widespread attention as a new type of nanofiller. CNTs have an extremely high aspect ratio and excellent mechanical properties. A small amount of CNTs can significantly improve the strength, modulus and conductivity of the matrix material. When combined with ABS / PC composite systems, it can not only toughen the ABS / PC composite system to further optimize the physical and mechanical properties of the material, but also give the material a certain electromagnetic shielding function, expanding its application range.
[0005] However, although adding PC and CNTs can significantly improve the comprehensive properties of ABS materials, it also brings some technical challenges. However, although carbon nanotubes can significantly improve some properties of the material, due to their extremely high surface activity, they are prone to agglomeration, which not only affects the uniformity of the composite material, but also may become a stress concentration point inside the material, which in turn reduces the toughness of the material.
[0006] Therefore, the applicant provides a weather-resistant ABS alloy and a preparation method thereof to overcome the aforementioned defects. Summary of the invention
[0007] The purpose of the present invention is to provide a weather-resistant ABS alloy and a preparation method thereof, so as to solve the technical problems mentioned in the above background technology.
[0008] The technical solution for achieving the purpose of the present invention is:
[0009] A weather-resistant ABS alloy comprises, by weight, 20 to 22 parts by weight of ABS, 60 to 66 parts by weight of modified polycarbonate, 4 to 6 parts by weight of modified carbon nanotubes, 0.2 to 0.4 parts by weight of antioxidant, and 0.5 to 1.5 parts by weight of acidic lubricant.
[0010] Furthermore, the antioxidant is antioxidant 168.
[0011] Furthermore, the modified polycarbonate is obtained by copolymerization of epoxy monomer and carbon dioxide.
[0012] Furthermore, the epoxy monomer is a composition of 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, octaepoxycyclohexylethyl cage-like polysilsesquioxane, and γ-glycidyloxypropylmethyldiethoxysilane.
[0013] Furthermore, the modified carbon nanotubes are obtained by modifying carbon nanotubes with a titanate coupling agent.
[0014] Furthermore, the titanate coupling agent is a composition of isopropyl dioleateoxy (dioctyl phosphate acyloxy titanate), isopropyl tris (dioctyl pyrophosphate acyloxy) titanate, and tetrabutyl titanate.
[0015] The present invention also provides a method for preparing a weather-resistant ABS alloy, comprising the following preparation steps:
[0016] (1) Weigh and prepare the following raw material components according to the following weight parts: 20-22 parts by weight of ABS, 60-66 parts by weight of modified polycarbonate, 4-6 parts by weight of modified carbon nanotubes, 0.2-0.4 parts by weight of antioxidant, and 0.5-1.5 parts by weight of acidic lubricant;
[0017] (2) 60 to 66 parts by weight of modified polycarbonate and 60 to 66 parts by weight of benzene are mixed and placed in a reaction kettle, and after high-speed stirring, a benzene suspension of modified carbon nanotubes is added dropwise, wherein the benzene suspension of modified carbon nanotubes contains 4 to 6 parts by weight of modified carbon nanotubes and 60 to 66 parts by weight of benzene; after the dropwise addition is completed, stirring is continued for 2.8 to 3.2 hours, and reduced pressure distillation is performed throughout the entire dropwise addition and reaction process, followed by rotary evaporation and drying to obtain a primary mixed material;
[0018] (3) 20 to 22 parts by weight of ABS are dried for 24 hours, then mixed evenly with the primary mixed material, 0.2 to 0.4 parts by weight of antioxidant, and 0.5 to 1.5 parts by weight of acidic lubricant, and then added to an extruder for extrusion granulation, and then the obtained particles are dried overnight to obtain a weather-resistant ABS alloy.
[0019] Furthermore, the preparation steps of the modified polycarbonate are as follows: adding epoxy monomer, catalyst SalenCoCl and co-catalyst PPNCl to a pre-dried high-pressure reactor, and filling with 3-4MPa CO2 at 25°C, stirring and reacting at 150-250rpm at 25°C for 24 hours to obtain modified polycarbonate; wherein the epoxy monomer uses 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, octaepoxycyclohexylethyl caged polysilsesquioxane, and γ-glycidyloxypropylmethyldiethoxysilane.
[0020] Furthermore, the mass ratio of the 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, octaepoxycyclohexylethyl caged polysilsesquioxane, and γ-glycidyloxypropylmethyldiethoxysilane is 10:4-6:84-86; the mass ratio of the epoxy monomer to the catalyst SalenCoCl and the co-catalyst PPNCl is 990-1010:1:1.
[0021] Furthermore, the preparation steps of the modified carbon nanotubes are as follows: 49 to 51 parts by mass of ferrous sulfate heptahydrate are dissolved in 200 parts by mass of distilled water, and then 5 parts by mass of multi-walled carbon nanotubes are added, ultrasonic oscillation is performed for 25 to 35 minutes, and then 148 to 152 parts by mass of hydrogen peroxide are added, and the reaction is stirred for 11.5 to 12.5 hours, and then the filtrate is filtered under reduced pressure, and the filtrate is rinsed with distilled water for many times until the filtrate is neutral, and then it is placed in a drying oven at 70°C for 24 hours to obtain hydroxylated carbon nanotubes; 3 parts by mass of hydroxylated carbon nanotubes, 160 parts by mass of ethanol, and 19 to 21 parts by mass of titanate coupling agent are mixed and placed in an ultrasonic cleaner for ultrasonic oscillation for 25 to 35 minutes. After the end of the ultrasound, the reaction is carried out at 74 to 76°C under stirring conditions for 3 to 5 hours, and the reaction is naturally cooled to room temperature after the reaction, and then the filtrate is filtered under reduced pressure, and the reaction solution is rinsed with anhydrous ethanol for many times to remove the unreacted titanate coupling agent in the reaction solution, and then it is placed in a drying oven at 70°C for 12 hours to obtain modified carbon nanotubes.
[0022] Furthermore, the titanate coupling agent includes isopropyl dioleate oxy (dioctyl phosphate titanate), isopropyl tri (dioctyl pyrophosphate titanate), and tetrabutyl titanate; the mass ratio of isopropyl dioleate oxy (dioctyl phosphate titanate), isopropyl tri (dioctyl pyrophosphate titanate), and tetrabutyl titanate is 1:1:1.5 to 2.5.
[0023] By adopting the above technical solution, the present invention has the following beneficial effects:
[0024] (1) The raw material components of the weather-resistant ABS alloy of the present invention include ABS, modified polycarbonate, modified carbon nanotubes, an antioxidant, and an acidic lubricant; wherein the modified carbon nanotubes are obtained by modifying carbon nanotubes with a titanate coupling agent, which can effectively improve the agglomeration problem of the carbon nanotubes and evenly disperse the carbon nanotubes in the weather-resistant ABS alloy, thereby ensuring the mechanical properties of the weather-resistant ABS alloy and effectively improving the strength and toughness of the weather-resistant ABS alloy.
[0025] (2) The modified polycarbonate of the present invention is prepared by copolymerizing 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, octaepoxycyclohexylethyl cage-like polysilsesquioxane, γ-glycidyloxypropylmethyldiethoxysilane and carbon dioxide to obtain a polysiloxane-polycarbonate block copolymer (Si-PC) having a dendritic structure; polysiloxane itself has natural flame retardancy, the decomposition gas generated during combustion is non-toxic, and it has excellent weather resistance, high and low temperature resistance and dielectric properties, and at the same time, its surface energy is extremely low, which helps to improve the mobility of the polymer chain segments, thereby exhibiting excellent impact resistance under low temperature conditions; however, the compatibility between polysiloxane and polycarbonate is poor, and direct mixing will lead to separation of the two phases, affecting the material properties; by block copolymerizing the above-mentioned specific siloxane monomer with PC, this problem can be effectively solved, so that the polysiloxane is evenly dispersed in the PC matrix, which not only improves the flame retardancy and low-temperature toughness of PC.
[0026] (3) The present invention first premixes the modified polycarbonate with a certain dendritic structure with the modified carbon nanotubes, and then adds ABS, an antioxidant and an acidic lubricant for compounding; during this process, the modified carbon nanotubes, the antioxidant and the acidic lubricant can be dispersed into the cavities formed by the modified polycarbonate with a dendritic structure, and the ABS can penetrate into these cavities and form physical crosslinks with the modified polycarbonate with a dendritic structure, thereby preliminarily increasing the compatibility between the modified polycarbonate and the ABS; the uncondensed carbon nanotubes The Ti-OH group can react with the unreacted silanol groups in the dendritic structure modified polycarbonate to generate polytitanium siloxane, which firmly grafts the modified carbon nanotubes onto the modified polycarbonate to form a stable chemical bond connection; this process not only strengthens the combination between the modified carbon nanotubes and the modified polycarbonate, but also further promotes the compatibility between the modified polycarbonate and ABS through the good compatibility of the modified carbon nanotubes and ABS, and the flame retardant properties, mechanical properties and weather resistance of the weather-resistant ABS alloy obtained are significantly improved. DETAILED DESCRIPTION
[0027] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0028] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention.
[0029] The following are some examples and comparative examples. The raw material components are as follows:
[0030] The ABS is made of PA-757 with a density of 1040kg / m 3 , Chi Mei Industrial Co., Ltd.
[0031] Multi-walled carbon nanotubes (MWCNTs): TNM3, outer diameter 10-20 nm, mass fraction >98%, Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences.
[0032] Acidic lubricant: AC 540A, the main component is ethylene acrylic acid copolymer, Honeywell International.
[0033] The catalyst SalenCoCl and the co-catalyst PPNCl were both obtained from Shanghai Anaiji Chemical Co., Ltd., and were: (R,R)-(-)-N,N'-bis(3,5-di-tert-butyl salicylidene)-1,2-cyclohexyldiamine cobalt and (bis-(triphenylphosphorane)ammonium chloride) respectively.
[0034] The PC used is PC-110 from Chi Mei Industrial Co., Ltd.
[0035] The remaining raw materials are commercially available.
[0036] Example 1
[0037] A method for preparing a weather-resistant ABS alloy comprises the following preparation steps:
[0038] (1) Weigh and prepare the following raw material components according to the following weight parts: 20 parts by weight of ABS, 60 parts by weight of modified polycarbonate, 4 parts by weight of modified carbon nanotubes, 0.2 parts by weight of antioxidant, and 0.5 parts by weight of acidic lubricant;
[0039] (2) 60 parts by weight of modified polycarbonate and 60 parts by weight of benzene were mixed and placed in a reaction kettle, stirred at 1000 rpm for 25 min, and then a benzene suspension of modified carbon nanotubes was added dropwise at 0.15 mL / min, wherein the benzene suspension of modified carbon nanotubes contained 4 parts by weight of modified carbon nanotubes and 60 parts by weight of benzene. After the dropwise addition was completed, stirring was continued for 2.8 h. The entire dropwise addition and reaction process was subjected to reduced pressure distillation, followed by rotary evaporation and drying to obtain a primary mixture;
[0040] (3) 20 parts by mass of ABS were dried at 90° C. for 24 h, then mixed evenly with the primary mixture, 0.2 parts by mass of antioxidant, and 0.5 parts by mass of acidic lubricant, and then added to an extruder for extrusion granulation. The extrusion temperatures were 80, 120, 230, 240, 240, 240, 240, 240, 240, 240° C. from the first zone to the tenth zone, respectively. The main engine speed was 500 r / min. The obtained particles were then dried at 100° C. overnight to obtain a weather-resistant ABS alloy.
[0041] The preparation steps of the modified polycarbonate are as follows: adding epoxy monomer, catalyst SalenCoCl and co-catalyst PPNCl to a pre-dried high-pressure reactor, charging 3MPaCO2 at 25°C, stirring and reacting at 150rpm for 24 hours at 25°C to obtain modified polycarbonate; wherein the epoxy monomer adopts 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, octaepoxycyclohexylethyl caged polysilsesquioxane, and γ-glycidyloxypropylmethyldiethoxysilane; the mass ratio of the 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, octaepoxycyclohexylethyl caged polysilsesquioxane, and γ-glycidyloxypropylmethyldiethoxysilane is 10:4:86; the mass ratio of the epoxy monomer to the catalyst SalenCoCl and the co-catalyst PPNCl is 990:1:1.
[0042] The preparation steps of the modified carbon nanotubes are as follows: 49 parts by mass of ferrous sulfate heptahydrate are dissolved in 200 parts by mass of distilled water, and then 5 parts by mass of multi-walled carbon nanotubes are added, ultrasonic oscillation is performed for 25 minutes, and then 148 parts by mass of hydrogen peroxide are added, and the reaction is stirred at 300 rpm for 11.5 hours, and then the filtrate is filtered under reduced pressure, and the filtrate is rinsed with distilled water for multiple times until the filtrate is neutral, and then placed in a drying oven at 70° C. for 24 hours to obtain hydroxylated carbon nanotubes; 3 parts by mass of hydroxylated carbon nanotubes, 160 parts by mass of ethanol, and 19 parts by mass of titanate coupling agent are mixed and placed in an ultrasonic cleaner for ultrasonic oscillation for 25 minutes. After the ultrasonic oscillation is completed, The reaction was carried out at 74°C and 800 rpm with stirring for 3 hours, and the reaction was naturally cooled to room temperature after the reaction, followed by vacuum filtration, and rinsed with anhydrous ethanol for multiple times to remove unreacted titanate coupling agent in the reaction solution, and then placed in a drying oven at 70°C for 12 hours to obtain modified carbon nanotubes; the titanate coupling agent includes isopropyl dioleate oxy (dioctyl phosphate acyloxy titanate), isopropyl tri (dioctyl pyrophosphate acyloxy) titanate, and tetrabutyl titanate; the mass ratio of isopropyl dioleate oxy (dioctyl phosphate acyloxy titanate), isopropyl tri (dioctyl pyrophosphate acyloxy) titanate, and tetrabutyl titanate is 1:1:1.5.
[0043] Example 2
[0044] A method for preparing a weather-resistant ABS alloy comprises the following preparation steps:
[0045] (1) Weigh and prepare the following raw material components according to the following weight parts: 21 parts by weight of ABS, 63 parts by weight of modified polycarbonate, 5 parts by weight of modified carbon nanotubes, 0.3 parts by weight of antioxidant, and 1 part by weight of acidic lubricant;
[0046] (2) 63 parts by mass of modified polycarbonate and 63 parts by mass of benzene were mixed and placed in a reaction kettle, stirred at 2000 rpm for 30 min, and then a benzene suspension of modified carbon nanotubes was added dropwise at 0.15 mL / min, wherein the benzene suspension of modified carbon nanotubes contained 5 parts by mass of modified carbon nanotubes and 63 parts by mass of benzene. After the dropwise addition was completed, stirring was continued for 3 h. The entire dropwise addition and reaction process was subjected to reduced pressure distillation, followed by rotary evaporation and drying to obtain a primary mixture;
[0047] (3) 21 parts by mass of ABS were dried at 90° C. for 24 h, then mixed evenly with the primary mixture, 0.3 parts by mass of antioxidant, and 1 part by mass of acidic lubricant, and then added to an extruder for extrusion granulation. The extrusion temperatures were 80, 120, 230, 240, 240, 240, 240, 240, 240, 240° C. from the first zone to the tenth zone, respectively. The main engine speed was 550 r / min. The obtained particles were then dried at 100° C. overnight to obtain a weather-resistant ABS alloy.
[0048] The preparation steps of the modified polycarbonate are as follows: adding epoxy monomer, catalyst SalenCoCl and co-catalyst PPNCl to a pre-dried high-pressure reactor, charging 3.5MPaCO2 at 25°C, stirring and reacting at 200rpm at 25°C for 24 hours to obtain modified polycarbonate; wherein the epoxy monomer adopts 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, octaepoxycyclohexylethyl caged polysilsesquioxane, and γ-glycidyloxypropylmethyldiethoxysilane; the mass ratio of the 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, octaepoxycyclohexylethyl caged polysilsesquioxane, and γ-glycidyloxypropylmethyldiethoxysilane is 10:5:85; the mass ratio of the epoxy monomer to the catalyst SalenCoCl and the co-catalyst PPNCl is 1000:1:1.
[0049] The preparation steps of the modified carbon nanotubes are as follows: 50 parts by mass of ferrous sulfate heptahydrate are dissolved in 200 parts by mass of distilled water, and then 5 parts by mass of multi-walled carbon nanotubes are added, and ultrasonic vibration is performed for 30 minutes, and then 150 parts by mass of hydrogen peroxide are added, and the reaction is stirred at 400 rpm for 12 hours, and then the filtrate is filtered under reduced pressure, and the filtrate is rinsed with distilled water for multiple times until the filtrate is neutral, and then placed in a drying oven at 70°C for 24 hours to obtain hydroxylated carbon nanotubes; 3 parts by mass of hydroxylated carbon nanotubes, 160 parts by mass of ethanol, and 20 parts by mass of titanate coupling agent are mixed and placed in an ultrasonic cleaner for ultrasonic vibration for 30 minutes. After the ultrasonic vibration is completed, the mixture is placed in an ultrasonic cleaner for ultrasonic vibration for 30 minutes. The reaction was carried out under stirring conditions of 5°C and 1000rpm for 4h, and the reaction was naturally cooled to room temperature after the reaction, followed by vacuum filtration, and rinsed with anhydrous ethanol for multiple times to remove unreacted titanate coupling agent in the reaction solution, and then placed in a drying oven at 70°C for 12h to obtain modified carbon nanotubes; the titanate coupling agent includes isopropyl dioleate oxy (dioctyl phosphate acyloxy titanate), isopropyl tri (dioctyl pyrophosphate acyloxy) titanate, and tetrabutyl titanate; the mass ratio of isopropyl dioleate oxy (dioctyl phosphate acyloxy titanate), isopropyl tri (dioctyl pyrophosphate acyloxy) titanate, and tetrabutyl titanate is 1:1:2.
[0050] Example 3
[0051] A method for preparing a weather-resistant ABS alloy comprises the following preparation steps:
[0052] (1) Weigh and prepare the following raw material components according to the following weight parts: 22 parts by weight of ABS, 66 parts by weight of modified polycarbonate, 6 parts by weight of modified carbon nanotubes, 0.4 parts by weight of antioxidant, and 1.5 parts by weight of acidic lubricant;
[0053] (2) 66 parts by weight of modified polycarbonate and 66 parts by weight of benzene were mixed and placed in a reaction kettle, stirred at 3000 rpm for 35 min, and then a benzene suspension of modified carbon nanotubes was added dropwise at 0.15 mL / min, wherein the benzene suspension of modified carbon nanotubes contained 6 parts by weight of modified carbon nanotubes and 66 parts by weight of benzene. After the addition was completed, stirring was continued for 3.2 h. The entire addition and reaction process was subjected to reduced pressure distillation, followed by rotary evaporation and drying to obtain a primary mixture;
[0054] (3) 22 parts by mass of ABS were dried at 90° C. for 24 h, then mixed evenly with the primary mixture, 0.4 parts by mass of antioxidant, and 1.5 parts by mass of acidic lubricant, and then added to an extruder for extrusion granulation. The extrusion temperatures were 80, 120, 230, 240, 240, 240, 240, 240, 240, 240° C. from the first zone to the tenth zone, respectively. The main engine speed was 600 r / min. The obtained particles were then dried at 100° C. overnight to obtain a weather-resistant ABS alloy.
[0055] The preparation steps of the modified polycarbonate are as follows: adding epoxy monomer, catalyst SalenCoCl and co-catalyst PPNCl to a pre-dried high-pressure reactor, and charging 4MPaCO2 at 25°C, stirring and reacting at 250rpm for 24 hours at 25°C to obtain modified polycarbonate; wherein the epoxy monomer adopts 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, octaepoxycyclohexylethyl caged polysilsesquioxane, and γ-glycidyloxypropylmethyldiethoxysilane; the mass ratio of the 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, octaepoxycyclohexylethyl caged polysilsesquioxane, and γ-glycidyloxypropylmethyldiethoxysilane is 10:6:84; the mass ratio of the epoxy monomer to the catalyst SalenCoCl and the co-catalyst PPNCl is 1010:1:1.
[0056] The preparation steps of the modified carbon nanotubes are as follows: 51 parts by mass of ferrous sulfate heptahydrate are dissolved in 200 parts by mass of distilled water, and then 5 parts by mass of multi-walled carbon nanotubes are added, ultrasonic oscillation is performed for 35 minutes, and then 152 parts by mass of hydrogen peroxide are added, and the reaction is stirred at 500 rpm for 12.5 hours, and then the filtrate is filtered under reduced pressure, and the filtrate is rinsed with distilled water for multiple times until the filtrate is neutral, and then placed in a drying oven at 70°C for 24 hours to obtain hydroxylated carbon nanotubes; 3 parts by mass of hydroxylated carbon nanotubes, 160 parts by mass of ethanol, and 21 parts by mass of titanate coupling agent are mixed and placed in an ultrasonic cleaner for ultrasonic oscillation for 35 minutes. After the ultrasonic oscillation is completed, the mixture is placed in an ultrasonic cleaner for ultrasonic oscillation for 35 minutes. The reaction was carried out under stirring conditions of 6°C and 1200rpm for 5h, and the reaction was naturally cooled to room temperature after the reaction, followed by vacuum filtration, and rinsed with anhydrous ethanol for multiple times to remove unreacted titanate coupling agent in the reaction solution, and then placed in a drying oven at 70°C for 12h to obtain modified carbon nanotubes; the titanate coupling agent includes isopropyl dioleate oxy (dioctyl phosphate acyloxy titanate), isopropyl tri (dioctyl pyrophosphate acyloxy) titanate, and tetrabutyl titanate; the mass ratio of isopropyl dioleate oxy (dioctyl phosphate acyloxy titanate), isopropyl tri (dioctyl pyrophosphate acyloxy) titanate, and tetrabutyl titanate is 1:1:2.5.
[0057] Comparative Example 1
[0058] The only difference between Comparative Example 1 and Example 2 is that the raw material components of the weather-resistant ABS alloy include, by weight, 21 parts by weight of ABS, 63 parts by weight of PC, 5 parts by weight of modified carbon nanotubes, 0.3 parts by weight of antioxidant, and 1 part by weight of acidic lubricant; the remaining steps and components are the same as those in Example 2.
[0059] Comparative Example 2
[0060] The only difference between Comparative Example 2 and Example 2 is that the raw material components of the weather-resistant ABS alloy, by weight, include: 21 parts by weight of ABS, 63 parts by weight of modified polycarbonate, 5 parts by weight of carbon nanotubes, 0.3 parts by weight of antioxidant, and 1 part by weight of acidic lubricant; the remaining steps and components are the same as those in Example 2.
[0061] Comparative Example 3
[0062] The difference between Comparative Example 3 and Example 2 is that the modified polycarbonate is obtained by mixing PC and polysiloxane; the remaining steps and components are the same as those in Example 2.
[0063] Comparative Example 4
[0064] The only difference between Comparative Example 4 and Example 2 is that the modified polycarbonate is obtained by copolymerization of 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, γ-glycidyloxypropylmethyldiethoxysilane and carbon dioxide; the remaining steps and components are the same as those in Example 2.
[0065] Comparative Example 5
[0066] The only difference between Comparative Example 5 and Example 2 is that the modified polycarbonate is obtained by copolymerization of 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, octaepoxycyclohexylethyl cage polysilsesquioxane, γ-glycidyloxypropyltriethoxysilane and carbon dioxide; the remaining steps and components are the same as those in Example 2.
[0067] Comparative Example 6
[0068] The difference between Comparative Example 6 and Example 2 is that the raw material components are directly mixed and granulated, specifically:
[0069] 21 parts by mass of ABS were dried at 90° C. for 24 hours, then mixed evenly with 63 parts by mass of modified polycarbonate, 5 parts by mass of modified carbon fiber, 0.3 parts by mass of antioxidant, and 1 part by mass of acidic lubricant, and added to an extruder for extrusion granulation. The extrusion temperatures were 80, 120, 230, 240, 240, 240, 240, 240, 240, 240° C. from the first zone to the tenth zone, respectively, and the main engine speed was 550 r / min. The obtained particles were then dried at 100° C. overnight to obtain a weather-resistant ABS alloy. The remaining steps and components were the same as those in Example 2.
[0070] Effect example
[0071] Impact property: The impact property is based on GB / T1043.1 standard. The notched impact strength of the weather-resistant ABS alloys prepared in the embodiments and comparative examples at room temperature and -40°C is tested by an impact testing machine. The load is set to 5.5J, the specimen size is 80*10*4mm, the notch depth is 2mm, and 5 specimens are tested. The final data is averaged. During the low-temperature test, the impact specimens are placed in a medical low-temperature refrigerator and frozen at the set temperature for 24 hours. After that, they are quickly taken out for testing. The test process of each specimen is completed within 10s.
[0072] Flame retardancy: The flame retardancy of the weather-resistant ABS alloys prepared in the examples and comparative examples was tested with reference to the U.S. ANSI / UL-94-1985 standard. The limiting oxygen index test was performed to determine the minimum oxygen concentration required for the weather-resistant ABS alloys prepared in the examples and comparative examples to maintain flaming combustion in a mixture of N2 and O2. The test was performed according to the ISO 4589-1996 standard, and the sample size was 120 mm×10 mm×4 mm.
[0073] Tensile properties: Referring to GB / T1040.2 standard, the weather-resistant ABS alloys prepared in the embodiments and comparative examples were subjected to a tensile test by a universal material testing machine; the specimen shape was dumbbell-shaped, with a total length of 170 mm and a thickness of 4 mm; the tensile rate was 50 mm / min, the tensile load was 1000 N, 5 specimens were tested, and the final data was averaged.
[0074] Weather resistance: tested in accordance with standard GB / T16422.2; black label temperature: 65°C, relative humidity 65%, irradiance (340nm): 0.50w / m 2 nm, cycle: continuous illumination, 102 min without spraying, 18 min with spraying, test time 200 h.
[0075] Table 1 shows the performance test results of the weather-resistant ABS alloys prepared in the examples and comparative examples.
[0076] Table 1
[0077]
[0078]
[0079] It can be seen from Table 1 that the weather-resistant ABS alloy of the present invention has good low-temperature toughness, good mechanical properties, good flame retardancy and good weather resistance.
[0080] Among them, compared with Example 2, Example 2 uses 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, octaepoxycyclohexylethyl caged polysilsesquioxane, γ-glycidyl ether oxypropylmethyldiethoxysilane and carbon dioxide to copolymerize to obtain a polysiloxane-polycarbonate block copolymer with a dendritic structure. The modified polycarbonate forms a physical crosslink with ABS through the dendritic structure, which enhances the toughness of the material. When the weather-resistant ABS alloy is subjected to external force, the stress concentration effect of the polysiloxane phase domain is most significant. The existence of stress concentration leads to the formation of a triaxial tensile stress between the PC matrix around the polysiloxane phase domain. force, thereby causing debonding at the interface between the polysiloxane phase domain and the surrounding PC matrix, generating a large number of holes. The appearance of a large number of holes can not only limit the formation and expansion of cracks in the PC matrix, but also weaken the constraint force of the PC matrix deformation in a low-temperature environment, thereby making it easier to produce forced high-elastic deformation of the PC matrix, thereby absorbing a large amount of impact energy and improving low-temperature toughness; and the subsequent modified polycarbonate reacts with the uncondensed Ti-OH groups on the modified carbon nanotubes to generate polytitanium siloxane, which strengthens the bonding between the modified carbon nanotubes and the modified polycarbonate. The weather-resistant ABS alloy of Example 2 has good low-temperature toughness, good mechanical properties, and good flame retardancy.
[0081] Compared with Example 2, Comparative Example 2 uses carbon nanotubes. There are compatibility issues between ABS, modified polycarbonate and carbon nanotubes. The weather-resistant ABS alloy of Example 2 has better low-temperature toughness, better mechanical properties, better flame retardancy and better weather resistance.
[0082] Compared with Example 2, the modified polycarbonate of Comparative Example 3 is obtained by mixing only PC and polysiloxane, and the compatibility between PC and polysiloxane is poor, and the compatibility between PC, polysiloxane and ABS is also poor. The weather-resistant ABS alloy of Example 2 has better low-temperature toughness, better mechanical properties, better flame retardancy and better weather resistance.
[0083] Comparative Example 4 is compared with Example 2. Comparative Example 4 is obtained by copolymerizing 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, γ-glycidyloxypropylmethyldiethoxysilane and carbon dioxide; a polysiloxane-polycarbonate block copolymer with a dendritic structure cannot be formed, and the crosslinking degree and compatibility of the weather-resistant ABS alloy are reduced. The weather-resistant ABS alloy of Example 2 has better low-temperature toughness and better mechanical properties.
[0084] Compared with Example 2, the modified polycarbonate in Comparative Example 5 is obtained by copolymerization of 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, octaepoxycyclohexylethyl cage polysilsesquioxane, γ-glycidyloxypropyltriethoxysilane and carbon dioxide. The crosslinking density in the weather-resistant ABS alloy is too high. The weather-resistant ABS alloy of Example 2 has better low-temperature toughness and better mechanical properties.
[0085] Compared with Example 2, Example 6 directly mixes the raw material components into granules without premixing and physical crosslinking. Polytitanium siloxane is not formed during the mixing process. The weather-resistant ABS alloy of Example 2 has better low-temperature toughness and better mechanical properties.
[0086] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A weather-resistant ABS alloy, characterized in that: The raw material components include, by weight: 20 to 22 parts by weight of ABS, 60 to 66 parts by weight of modified polycarbonate, 4 to 6 parts by weight of modified carbon nanotubes, 0.2 to 0.4 parts by weight of antioxidant, and 0.5 to 1.5 parts by weight of acidic lubricant.
2. The weather-resistant ABS alloy according to claim 1, characterized in that: The modified polycarbonate is obtained by copolymerizing epoxy monomer and carbon dioxide.
3. The weather-resistant ABS alloy according to claim 2, characterized in that: The epoxy monomer is a composition of 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, octaepoxycyclohexylethyl cage-like polysilsesquioxane and gamma-glycidyl ether oxypropylmethyldiethoxysilane.
4. The weather-resistant ABS alloy according to claim 1, characterized in that: The modified carbon nanotubes are obtained by modifying the carbon nanotubes with a titanate coupling agent.
5. The weather-resistant ABS alloy according to claim 4, characterized in that: The titanate coupling agent is a composition of isopropyl dioleate oxy (dioctyl phosphate acyloxy titanate), isopropyl tri (dioctyl pyrophosphate acyloxy) titanate and tetrabutyl titanate.
6. A method for preparing a weather-resistant ABS alloy, characterized in that: The method comprises the following preparation steps: (1) Weighing and preparing the materials according to the weight proportions and raw material components described in claim 1; (2) 60 to 66 parts by weight of modified polycarbonate and 60 to 66 parts by weight of benzene are mixed and placed in a reaction kettle, and after high-speed stirring, a benzene suspension of modified carbon nanotubes is added dropwise, wherein the benzene suspension of modified carbon nanotubes contains 4 to 6 parts by weight of modified carbon nanotubes and 60 to 66 parts by weight of benzene; after the dropwise addition is completed, stirring is continued for 2.8 to 3.2 hours, and reduced pressure distillation is performed throughout the entire dropwise addition and reaction process, followed by rotary evaporation and drying to obtain a primary mixed material; (3) 20 to 22 parts by weight of ABS are dried for 24 hours, then mixed evenly with the primary mixed material, 0.2 to 0.4 parts by weight of antioxidant, and 0.5 to 1.5 parts by weight of acidic lubricant, and then added to an extruder for extrusion granulation, and then the obtained particles are dried overnight to obtain a weather-resistant ABS alloy.
7. The method for preparing the weather-resistant ABS alloy according to claim 6, characterized in that: The preparation steps of the modified polycarbonate are as follows: adding epoxy monomer, catalyst SalenCoCl and co-catalyst PPNCl into a pre-dried high-pressure reactor, and charging 3-4MPa CO2 at 25°C, stirring and reacting at 150-250rpm at 25°C for 24 hours to obtain modified polycarbonate; wherein the epoxy monomer is 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, octaepoxycyclohexylethyl caged polysilsesquioxane, and γ-glycidyloxypropylmethyldiethoxysilane.
8. The method for preparing the weather-resistant ABS alloy according to claim 7, characterized in that: The mass ratio of the 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, octaepoxycyclohexylethyl caged polysilsesquioxane, and γ-glycidyloxypropylmethyldiethoxysilane is 10:4-6:84-86; the mass ratio of the epoxy monomer to the catalyst SalenCoCl and the co-catalyst PPNCl is 990-1010:1:
1.
9. The method for preparing the weather-resistant ABS alloy according to claim 6, characterized in that: The preparation steps of the modified carbon nanotubes are as follows: dissolving 49 to 51 parts by weight of ferrous sulfate heptahydrate in 200 parts by weight of distilled water, then adding 5 parts by weight of multi-walled carbon nanotubes, ultrasonically oscillating for 25 to 35 minutes, then adding 148 to 152 parts by weight of hydrogen peroxide, stirring and reacting for 11.5 to 12.5 hours, then vacuum-filtering, rinsing with distilled water for multiple times until the filtrate is neutral, then drying in a drying oven at 70° C. for 24 hours to obtain hydroxylated carbon nanotubes; taking 3 parts by weight of hydroxylated carbon nanotubes, 160 parts by weight of ethanol, and 19 to 21 parts by weight of titanate coupling agent, mixing them, placing them in an ultrasonic cleaner for ultrasonic oscillation for 25 to 35 minutes, after the end of the ultrasonic wave, reacting at 74 to 76° C. under stirring conditions for 3 to 5 hours, cooling naturally to room temperature after the reaction, then vacuum-filtering, rinsing with anhydrous ethanol for multiple times to remove unreacted titanate coupling agent in the reaction solution, and then drying them in a drying oven at 70° C. for 12 hours to obtain modified carbon nanotubes.
10. The method for preparing the weather-resistant ABS alloy according to claim 6, characterized in that: The titanate coupling agent includes isopropyl dioleate oxy (dioctyl phosphate acyloxy titanate), isopropyl tri (dioctyl pyrophosphate acyloxy) titanate, and tetrabutyl titanate; the mass ratio of isopropyl dioleate oxy (dioctyl phosphate acyloxy titanate), isopropyl tri (dioctyl pyrophosphate acyloxy) titanate, and tetrabutyl titanate is 1:1:1.5-2.5.
Citation Information
Patent Citations
Aliphatic polycarbonate composite material and preparation method thereof
CN106543423A
Flame-retardant weather-resistant polycarbonate composite new material and preparation process thereof
CN117285809A
Apparatus for cutting inside of an object
KR102254835B1
Cited By
FDM 3D printing refraction laser effect material and preparation method thereof
CN120118506A